The effect of a roving nurse mentor on household coverage and quality of care provided by community health worker teams in South Africa: a longitudinal study with a before, after and 6 months post design - Jane Goudge; Olukemi Babalola; Hlologelo Malatji; Jonathan Levin; Margaret Thorogood; Frances Griffiths (BMC, 2023)
Abstract Objective Community health workers (CHW) are undertaking more complex tasks as part of the move towards universal health coverage in many low- and middle-income settings. They are expected to provide promotive and preventative care, make referrals to the local clinic, and follow up on non-attendees for a range of health conditions. CHW programmes can improve access to care for vulnerable communities, but many such programmes struggle due to inadequate supervision, low levels of CHW literacy, and the marginalized status of CHW in the health system. In this paper, we assess the effect of a roving nurse mentor on the coverage and quality of care of the CHW service in two vulnerable communities in South Africa. Participants CHW, their supervisors, household members. Intervention Roving professional nurse mentor to build skills of supervisors and CHW teams. Methods Three household surveys to assess household coverage of the CHW service (baseline, end of the intervention, and 6 months after end of intervention); structured observations of CHW working in households to assess quality of care. Results The intervention led to a sustained 50% increase in the number of households visited by a CHW in the last year. While the proportion of appropriate health messages given to household members by CHW remained constant at approximately 50%, CHW performed a greater range of more complex tasks. They were more likely to visit new households to assess health needs and register the household in the programme, to provide care to pregnant women, children and people who had withdrawn from care. CHW were more likely to discuss with clients the barriers they were facing in accessing care and take notes during a visit. Conclusion A nurse mentor can have a significant effect both on the quantity and quality of CHW work, allowing them to achieve their potential despite their marginalised status in the health system and their limited prior educational achievement. Supportive supervision is important in enabling the benefit of having a health cadre embedded in marginalised communities to be realised.